A New Vent Limpet in the Genus Lepetodrilus (Gastropoda: Lepetodrilidae) From Southern Ocean Hydrothermal Vent Fields Showing High Phenotypic Plasticity - Linse, Katrin; Roterman, Christopher Nicolai; Chen, Chong (Frontiers in Marine Science, 2019)
The recently discovered hydrothermal vent ecosystems in the Southern Ocean host a suite of vent-endemic species, including lepetodrilid limpets dominating in abundance. Limpets were collected from the chimneys, basalts and megafauna of the East Scotia Ridge segments E2 and E9 and the Kemp Caldera at the southern end of the South Sandwich Island arc. The limpets varied in size and shell morphology between vent fields and displayed a high degree of phenotypic plasticity. Size frequency analyses between vent fields suggests continuous reproduction in the limpet and irregular colonisation events. Phylogenetic reconstructions and comparisons of mitochondrial COI gene sequences revealed a level of genetic similarity between individuals from the three vent fields consistent with their belonging to a single molecular operational taxonomic unit. Here we describe Lepetodrilus concentricus n. sp., and evaluate its genetic distinctness and pylogenetic position with congeners based on the mitochondrial COI gene. Results indicate that L. concentricus n. sp. is a sister species towith the two species estimated to have diverged within the last ~5 million years.